Family matters: James Dobson and Focus on the Family's crusade for the Christian home - Stephens, Hilde Løvdal (Religion and American culture, 2019)
Sex and civilization -- Evangelical parenting -- Sex education is a family affair -- Family values and the problem of race in America -- God and gays.